Domino Reactions of Chromones with Heterocyclic Enamines - Langer, Peter (Synlett, 2021)
Domino reactions of heterocyclic enamines with chromone derivatives provides a convenient synthesis of a great variety of annulated heterocyclic ring systems. The course of the reaction depends on the type of substituent located at position 3 of the chromone. Reactions of 3-unsubstituted chromones, 3-nitrochromones, and 3-halochromones proceed by conjugate addition of the carbon atom of the enamine to carbon C-2 of the chromone, ring cleavage, and recyclization via the chromone carbonyl group. In the case of 3-formylchromes, 3-dichloroacetylchromone, 3-perfluoroalkanoylthiochromones, 3-(2-fluorobenzoyl)chromones, and 3-methoxalylchromones the final cyclization proceeds via the carbonyl group located outside the chromone moiety. The functional groups located at the carbonyl group at position 3 of the chromone allow for further synthetic transformations including additional ring closures.Contents1 Introduction2 3-Unsubstituted Chromones3 3-Nitrochromones4 3-Formylchromes5 3-Dichloroacetylchromone6 3-Perfluoroalkanoylthiochromones7 3-Methoxalylchromones8 3-(2-Fluorobenzoyl)chromones9 3-Halochromones10 Chromone-3-carboxylic Acids11 Conclusions
Keywords: chromones; enamines; domino reactions; cyclization; heterocycles